Paraventricular Vitamin D Receptors Are Required for Glucose Tolerance in Males but Not Females - Beck, Jessie; da Silva Teixeira, Silvania; Harrison, Keisha; Phillips, Gabrielle; He, Yanlin; Sisley, Stephanie (Frontiers in Endocrinology, 2022)
When delivered directly into the brain, vitamin D, can improve glucose levels in male mice. Additionally, the loss of the vitamin D receptor (VDR) in male mice’s paraventricular hypothalamus (PVH) results in impaired glucose tolerance. Data in humans shows that low vitamin D levels are detrimental to glucose homeostasis, an effect that may be more prominent in men. However, it is unknown if vitamin D action in the brain is required for normal glucose regulation in female mice. This study shows that in both viral and genetic models, male mice with obesity and PVH VDR loss have impaired glucose tolerance while female mice are unaffected. Weights were unaltered in both sexes by PVH VDR loss. Additionally, PVH VDR loss did not cause any glucose abnormalities in either sex when the mice were on a chow diet. Utilizing electrophysiology studies, we show PVH VDR loss resulted in decreased baseline firing frequency and resting membrane potential in males, but not females. Additionally, male mice with PVH VDR loss had impaired miniature excitatory postsynaptic currents (mEPSC), while females were unaffected. Interestingly, the PVH neurons of both sexes were activated by exogenous vitamin D (1,25-dihydroxyvitamin D3), an effect dependent upon the VDR. Thus, there is sexual dimorphism, for the actions of the PVH VDR on glucose regulation. PVH VDRs are necessary for normal glucose homeostasis in males but not females and this may be secondary to actions of the VDR on neuronal activity.